Restructuring Russian Christian Personal Names in the Pre-National Period: Names in -y - Irina Mikhailovna Ganzhina (Вопросы ономастики, 2024)
This article is the concluding part of a series of articles investigating the derivation of the geographically limited system of Christian personal name forms during the pre-national period. Drawing on anthroponyms from Tver business texts of the 16th–17th centuries, it explores the structural reorganization of full male personal names in colloquial speech. The focus of the analysis is on the productive paradigmatic class *-jŏ, specifically full forms of anthroponyms with a soft base (ending in -y) in different variants: -iy, -ey, -ay, -oy. During the period studied, these colloquial full forms were highly diverse, with numerous phonetic and morphological variants. These variants primarily emerged from fictitious segmentation and formal alteration of the anthroponymic bases. At the same time, preference in documents is given to colloquial rather than canonical forms, which were used mainly by clergymen. The article identifies the word-formation mechanisms that facilitated the integration of foreign personal names into the Russian onomastic system, leading to the development of numerous colloquial full forms of names, particularly through structural reorganization and formal-associative relationships involving modifications to the final segment of the name. These structural transformations, combined with phonetic changes, create a unique anthroponymic pattern specific to each territory. The analysis reveals that in the 16th–17th centuries Tver documents, two forms of Christian personal names were particularly stable and frequently recurring: consonant-final truncated forms (e.g., Vlas, Nazar, Taras, Fedos) and forms ending in -ey (e.g., Vlasey, Nazarey, Tarasey, Fedosey).